Colistin-resistance and carbapenemase-producing among carbapenem-resistance E. coli and K. pneumoniae - Ngá»c BÃch Tráº§n; Phu Thien Truong; Loc Tran Mai Nguyen; Dang Ngoc Tran; Thao Thi Ngoc Nguyen; Phuong Thi Nam Nguyen; Tuan Anh Dang; Van Thi Hue Tran; Dat Quoc Ngo (Revista Cubana de Medicina Militar)
Introduction: Carbapenemase-producing Enterobacterales (CPE) is one of the causes of community health-threatening, most common in Escherichia coli and Klebsiella pneumoniae. CPE has appeared in many countries, especially developing ones, but it has not been recognized in routine antibiograms. Also, assessing colistin susceptibility is a significant obstacle for both diagnostic and epidemiological because of technical difficulties. There is rare data about CPE and colistin-resistant Enterobacterales. Objectives: Determine the prevalence of producing carbapenemase and colistin-resistance among K. pneumoniae and E. coli resistant to carbapenems. Methods: In a cross-sectional survey, 129 K. pneumoniae and 31 E. coli strains, which demonstrated carbapenem resistance, were collected from inpatients at Cho Ray Hospital over a three-month period. Carbapenemase production was detected using the modified carbapenem inactivation method and EDTA-modified carbapenem inactivation method, and colistin resistance was detected using the broth microdilution method according to CLSI M100S34. Results: Of 160 participants' strains, 80% of carbapenemase-producing K. pneumoniae and E. coli were detected; among these, Metallo beta-lactamase-producing was taken 69,5%. Of 31 colistin-resistant, 30 were K. pneumoniae, and only 1 E. coli was detected that was resistant to colistin. Conclusion: Among participants' strains, carbapenemase-producing prevalence was very high. There were signs of a widespread extensively drug-resistant K. pneumoniae. Most of E. coliwas susceptible to colistin.